2012
DOI: 10.1590/s0102-86502012000200001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term following-up of viability of spleen autotransplants in the Beagle canine model

Abstract: PURPOSE: To examine the possible late complications of splenectomy or spleen autotransplantation in large laboratory animal model, in which we need non-invasive or minimal-invasive methods for long-term monitoring of the experimental animals. METHODS: Experimental groups of beagle dogs were: non-operated control, sham-operated control, splenectomy, spleen autotransplantation with 5 or 10 spleen-chips taken into the greater omentum (Furka's technique). Prior to operations, on the 1st postoperative week,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In addition to these functions, the participation of the spleen in metabolic control is receiving increasing attention [1][2][3][4][5][6][7][8][9] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these functions, the participation of the spleen in metabolic control is receiving increasing attention [1][2][3][4][5][6][7][8][9] .…”
Section: Discussionmentioning
confidence: 99%
“…The functions of the spleen are part of the organic metabolism and disorders of this organ are related to different diseases [1][2][3][4][5][6][7][8][9][10] and Fabry disease also present spleen manifestations 10 . The spleen participates in the metabolism of all metals, of albuminoids and of indirect bilirubin from phagocytized red blood cells 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…The scintigraphic images recorded the radiotracer uptake by splenic implants with difficulty due to the overlapping of liver image 13 . However, the emission of radiation dosages by implanted spleen fragments left no doubt that 12 weeks were sufficient for their phagocytic functional recovery 13,14 .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…The scintigraphic images recorded the radiotracer uptake by splenic implants with difficulty due to the overlapping of liver image 13 . However, the emission of radiation dosages by implanted spleen fragments left no doubt that 12 weeks were sufficient for their phagocytic functional recovery 13,14 . There was no difference between the conservation of liquids studied in relation to the evaluation of the function of the splenic implants by scintigraphy, which is a more sensitive method to indicate uptake by spleen cells than the blood tests 14 .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…In clinical trials, Immunoprophylaxis, chemoprophylaxis and spleen preserving surgery such as resection of the spleen and splenic autotransplantation along with informing and training patients prevented many serious complications [7]. Some studies have suggested the autotransplantation of homogenized spleen tissue.…”
Section: Introductionmentioning
confidence: 99%